2016
DOI: 10.1371/journal.pone.0162436
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of a Wrist- and Hip-Worn Actigraph Accelerometer in 4-Year-Old Children

Abstract: IntroductionTo determine time spent at different physical activity intensities, accelerometers need calibration. The aim of this study was to develop and cross-validate intensity thresholds for the Actigraph GT3X+ accelerometer for wrist and hip placement in four-year-old children.MethodsIn total 30 children (49 months, SD 3.7) were recruited from five preschools in Stockholm. Equipped with an accelerometer on the wrist and another on the hip, children performed three indoor activities and one free-play sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 28 publications
(58 reference statements)
6
68
1
1
Order By: Relevance
“…Research has looked at the difference between wearing a wrist and hip accelerometer on preschool children and one study in Scotland found that wrist-worn accelerometers provided a valid estimate of total physical activity, whereas hip-worn accelerometers showed a reasonable agreement to cut-points [68]. This was supported by a study in Stockholm, Sweden, which similarly monitored preschool children and found that wrist-worn accelerometers performed more accurately when assessing time spent in sedentary, light activity and MVPA, when compared to hip-worn accelerometers [69]. In terms a study by Johannsson et al [69], however, there were stark differences between the mean (SD) counts measured over 5 s for wrist and hip activity, with the vector magnitude (a combined measure of the three axes, x, y and z) when watching a cartoon measuring 91 (73) for the wrist and 14 (15) for the hip, and when dancing, the 1093 (330) was measured for the wrist and 396 (148) for the hip.…”
Section: Discussionmentioning
confidence: 90%
“…Research has looked at the difference between wearing a wrist and hip accelerometer on preschool children and one study in Scotland found that wrist-worn accelerometers provided a valid estimate of total physical activity, whereas hip-worn accelerometers showed a reasonable agreement to cut-points [68]. This was supported by a study in Stockholm, Sweden, which similarly monitored preschool children and found that wrist-worn accelerometers performed more accurately when assessing time spent in sedentary, light activity and MVPA, when compared to hip-worn accelerometers [69]. In terms a study by Johannsson et al [69], however, there were stark differences between the mean (SD) counts measured over 5 s for wrist and hip activity, with the vector magnitude (a combined measure of the three axes, x, y and z) when watching a cartoon measuring 91 (73) for the wrist and 14 (15) for the hip, and when dancing, the 1093 (330) was measured for the wrist and 396 (148) for the hip.…”
Section: Discussionmentioning
confidence: 90%
“…Study strengths are the large sample of four- to six-year-old children that provided valid pedometer data, and the cluster randomised controlled trial with a pre-test post-test design. However, future studies could look into objectively measuring four- to six-year-olds’ PA by using hip and wrist accelerometers simultaneously as wrist-worn accelerometers have shown to measure different PA intensities more accurately [ 48 ]. Another strength is the use of process evaluation questionnaires for both kindergarten teachers and parents/caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity data were considered valid if the wear time was at least two schooldays and one non‐school day for a minimum of 14 hours a day. The units have been validated and are considered reliable for estimating adolescents’ physical activity . Physical activity parameters were derived from ActiLive software, version 6.13.0 (Actigraph Inc).…”
Section: Methodsmentioning
confidence: 99%